PEMBERDAYAAN MASYARAKAT MELALUI KEGIATAN PEMBERSIHAN SUNGAI OLEH MAHASISWA BERBASIS ASSET-BASED COMMUNITY DEVELOPMENT (ABCD) - Adi Herisasono; Nana Mursyida Arifiana; Haniyah Haniyah; Pratolo Saktiawan; Elly Christanty Gautama (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2026)
River cleanup activities by students are a form of community service aimed at improving environmental quality and building ecological awareness. This program is implemented through Asset-Based Community Development (ABCD), which utilizes local assets, such as a culture of mutual cooperation, leadership, and village facilities, to encourage participation. Activities include identifying river problems, joint cleanup actions with residents, and education on the impact of waste on the environment. The results show improvements in river conditions, increased awareness of the importance of protecting rivers, and the establishment of sustainable cooperation between students, the government, and residents. In addition, this activity serves as an educational tool that encourages long-term behavioral change, so that the community better understands that environmental preservation is a shared responsibility. This shows that the involvement of students as agents of change can be a major driver in empowering the community to protect the river ecosystem in a sustainable manner.